Association of CYP2J2 gene polymorphisms with ischemic stroke - Li, Qing (Int J Clin Exp Med, 2015)
Objective: The present study aims to investigate the relationship between CYP2J2 gene polymorphisms and ischemic stroke (IS) in a Chinese Han population. Methods: We performed a case-control study including 300 stroke patients and 300 healthy control subjects to compare the distribution of genetic polymorphism G-50T in CYP2J2 gene. Results: We found GT genotype of G-50T in CYP2J2 gene was associated with the risk for IS (13.7% vs. 7.7%, P = 0.037). After adjustment of confounders, the difference remains significant (OR = 1.890, 95% CI: 1.042-3.011). Conclusion: CYP2J2 gene polymorphism might increase the risk of stroke in Chinese population.